2018
DOI: 10.1590/2317-1782/20182017071
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with mouth breathing diagnosis in children based on a multidisciplinary assessment

Abstract: We concluded that a multidisciplinary diagnosis is important, given that each evaluation domain, including OTRL, dental and speech therapy, presented variables associated with MB diagnosis. Body posture and nasal patency variables were not associated with MB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 28 publications
2
32
0
9
Order By: Relevance
“…Facial changes in mouth breather are caused due to a number of factors that involve muscle and bone structures. There are studies (14,15,17) that show the pattern of vertical facial growth and the convex face. Altered facial patterns are a common feature and could be seen by most teachers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Facial changes in mouth breather are caused due to a number of factors that involve muscle and bone structures. There are studies (14,15,17) that show the pattern of vertical facial growth and the convex face. Altered facial patterns are a common feature and could be seen by most teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the possibility of dental alterations (Q6) caused by mouth breathing, 67.3% of teachers answered in the pre-program questionnaire that mouth breathing may cause dental changes, and 97.3% in the post questionnaire, which reveals the effectiveness of the Speech Therapy Orientation Program. Studies have shown that dental occlusion can undergo changes in people who breathe through the mouth, with increased dental overjet, crossed bite, open bite, increased vertical overlap, ogival palate and maxillary atresia (15)(16)(17) . Dental changes are related to a series of consequences of the functions of the stomatognathic system, such as chewing, swallowing and even speech.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouth breathing may due to genetic factors, poor oral habits, or nasal obstruction, including but not limited to adenoid/tonsil hypertrophy, nasal polyps, nasal septum deviation, turbinate hypertrophy, or sinusitis. [1][2][3][4][5][6]. In addition, mouth breathing may be related to respiratory allergies, climatic conditions, a poor sleeping position, breastfeeding [7].…”
Section: Introductionmentioning
confidence: 99%